Sanksi Pidana Terhadap Pelaku Tindak Pidana Penjualan Jimat - Luh Gede Anglika Gayatri Sukma; I Made Sepud; I Nyoman Subamia (Jurnal Analogi Hukum, 2024)
The sale of amulets in the community is very troubling because many lead to fraud. The sale of amulets in the Criminal Code has been regulated in Article 546 of the Criminal Code but, in practice, it is charged with Article 378 of the Criminal Code on fraud. The formulation of the problem in this study, namely how is the regulation of the criminal act of selling amulets in positive law in Indonesia? and how are the criminal sanctions against the perpetrators of the criminal act of selling amulets? This type of research is normative with the approach of legislation and concepts. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials by means of documentation and notes. Analysis of legal materials is descriptive and analytical. The results of this study are that the seller of amulets is threatened with a maximum imprisonment of three months or a maximum fine of four thousand five hundred rupiahs, but in practice the perpetrators of selling amulets are more often subject to Article 378 of the Criminal Code on fraud which proves that Article 546 of the Criminal Code is no longer relevant in society.